From dust to stardust : a novel - Rooney, Kathleen, 1980- (Lake Union Publishing, 2023)
"Chicago, 1916. Doreen O'Dare is fourteen years old when she hops a Hollywood-bound train with her beloved Irish grandmother. Within a decade, her trademark bob and insouciant charm make her the preeminent movie flapper of the Jazz Age. But her success story masks one of relentless ambition, tragedy, and the secrets of a dangerous marriage. Her professional life in flux, Doreen trades one dream for another. She pours her wealth and creative energy into a singular achievement: the construction of a one-ton miniature Fairy Castle, the likes of which the world has never seen. So begins Doreen's public tour to lift the nation's spirits during the Great Depression--and a personal journey worth remembering. A sweeping journey from the dawn of the motion picture era through turbulent twentieth-century America, From Dust to Stardust is a breathtaking novel about one determined woman navigating change, challenging the price of fame, and sharing the gift of real magic"--